Blockchain in healthcare applications: Research challenges and opportunities - McGhin, Thomas; Choo, Kim-Kwang Raymond; Liu, Charles Zhechao; He, Debiao (Journal of network and computer applications, 2019)
Blockchain has a range of built-in features, such as distributed ledger, decentralized storage, authentication, security, and immutability, and has moved beyond hype to practical applications in industry sectors such as Healthcare. Blockchain applications in the healthcare sector generally require more stringent authentication, interoperability, and record sharing requirements, due to exacting legal requirements, such as Health Insurance Portability and Accountability Act of 1996 (HIPAA). Building on existing blockchain technologies, researchers in both academia and industry have started to explore applications that are geared toward healthcare use. These applications include smart contracts, fraud detection, and identity verification. Even with these improvements, there are still concerns as blockchain technology has its own specific vulnerabilities and issues that need to be addressed, such as mining incentives, mining attacks, and key management. Additionally, many of the healthcare applications have unique requirements that are not addressed by many of the blockchain experiments being explored, as highlighted in this survey paper. A number of potential research opportunities are also discussed in this paper.